Citogenética molecular de Astyanax scabripinnis (Characidae, Incertae sedis) enfase no cromossomo B. - Pistune, Helena Flávia de Mello (2010)
The origin, maintenance and frequency of B chromosomes present in some population of Astyanax have been arousing interest of cytogeneticists groups about a possible beneficial or deleterious effect for the species. These chromosomes generally shows intra and interindividual numerical variation. The aim of this work was to perform a cytogenetical analysis on the origin and molecular differentiation of the B chromosomes of Astyanax scabripinnis from “Das Pedras” stream, Campos do Jordão, SP. The analysis showed a diploid number of 50 chromosomes, karyotypic formula 6m, 22sm, 10st and 12a, besides the intra and interindividual variation of a B macrochromosome. The heterochromatic B macrochromosome shows shape and size similar to the major pair of the A complement (1st metacentric pair). In spermatogonial metaphase was possible to observe three great metacentric chromosomes in cells with 2n=51 chromosomes. However, was observed in pachitene cells with 26 chromosomical elements only one great bivalent, showing that the B chromosome performs arm-to-arm pairing. In situ localization with a B chromosome probe showed this element entirely marked, in addittion to small pericentromerics and terminal sites in the A chromosomes complement, among them, the 24th pair. Besides, the As51 probe showed localization in the major part of the B chromosome, and also 14 autossomical sites. Between the As51 sites there is an interstitial marking in the long arm of the 24th acrocentric pair. On the other hand, the localization of the repetitive sequences Cot-1 DNA, obtained from individuals without B chromosome, showed signals on the pericentromeric and terminal regions of almost all chromosomes, including the B chromosome and the 24th pair. No rDNA site was observed on B chromosome. This data corroborate the hypothesis of the origin of B chromosome through the formation of an isochromosome of the 24th acrocentric pair. Even, the cytogenetical analysis in meiotic cells shows that the B chromosome performs arm-to-arm pairing, a mechanism that can contribute to the transposition of sequences, rising thus the molecular differentiation of the B chromosome in relation to the A complement. Therefore, this work contributes to a better comprehension of the molecular nature of the B chromosome in A. scabripinnis, as well as its origin and evolutionary trends.